Mortality, appropriate and inappropriate shocks - observations from an institutional implantable cardioverter defibrillator registry. (24th May 2021) - Prepolec, I; Pasara, V; Ciglenecki, E; Bogdanic, JE; Putric Posavec, J; Pezo-Nikolic, B; Matasic, R; Krpan, M; Lovric-Bencic, M; Puljevic, M; Puljevic, D; Milicic, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Implantable cardioverter defibrillator (ICD) is an effective therapy for primary (PP) and secondary prevention (SP) of sudden cardiac death (SCD). ICD adverse events include inappropriate shocks (IS), device infection and failure.  Methods: We analysed the data concerning all newly implanted ICDs in our institution from 2011 to 2017. Follow-up data was collected until the end of 2019. Results: In total, 507 ICDs were implanted (85.4% male, 57.6 ± 14.0 years-old), 375 (74.0%) for PP and 132 (26.0%) for SP. The mean follow-up was 34.3 ± 23.8 months. ICD delivered therapy in 42.4% of SP and in 28.8% of PP patients (p = 0.15). In PP, shocks were delivered in 25.7% of non-ischaemic heart disease (NIHD) and in 17.6% ischaemic heart disease (IHD) patients (p = 0.81). IS were significantly more common in NIHD patients (13.8% vs 2.4% in IHD group, p < 0.0001). PP patients with NIHD also had a higher shock burden (average of 8.0 ± 17.4 shocks compared to 2.7 ± 3.0 in the IHD group). However, it failed to reach the level of statistical significance (p = 0.052). In SP, the rate of ICD activation and that of IS were similar in both groups (IHD and NIHD). In total, 32.6% of SP patients received appropriate shock (AS) and 5.3% of them received at least one IS (average number of AS and IS being 8.7 ± 11.5 and 1.1 ± 0.4 respectively). Mortality was significantly higher in SP than in PP (34.8% vs 13.9%, p < 0.001). In PP, significantly more deaths occurred among IHD than NIHD patients (18.8% vs 10.0%, p < 0.001).  Conclusion: The prevalence of AS and IS was relatively higher than reported elsewhere. Same was true for mortality. Interestingly, the rate of IS was somewhat higher in NIHD than in IHD, which was unexpected.